2019
DOI: 10.3390/nu11040747
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcopenic Obesity: Current Knowledge, Revised Identification Criteria and Treatment Principles

Abstract: Osteosarcopenic obesity (OSO) syndrome describes the simultaneous deterioration of bone, muscle and excess fat, resulting in reduced functionality and systemic metabolic dysregulation. The key component contributing to this may be ectopic fat in the viscera, bone and muscle. OSO research to date is summarized, and the revised criteria for its identification for research purposes are reviewed and proposed, including new criteria to assess visceral fat in males and females. Finally, nutritional and physical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 141 publications
(226 reference statements)
3
116
0
6
Order By: Relevance
“…Literature searches were performed using combination of key-words and the use of Boolean AND, to include chronic stress with inflammation, immune system, chronic diseases, adiposity/obesity and nutrition. The most recent review and update on the osteosarcopenic obesity diagnostic criteria, characteristics and treatment principles was published in 2019 by Kelly et al [22]. Therefore, the references from that paper were explored and the phrase "osteosarcopenic obesity" was used in the search to capture any relevant articles published in the meantime.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature searches were performed using combination of key-words and the use of Boolean AND, to include chronic stress with inflammation, immune system, chronic diseases, adiposity/obesity and nutrition. The most recent review and update on the osteosarcopenic obesity diagnostic criteria, characteristics and treatment principles was published in 2019 by Kelly et al [22]. Therefore, the references from that paper were explored and the phrase "osteosarcopenic obesity" was used in the search to capture any relevant articles published in the meantime.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, it has been recognized and studied throughout the world in different populations, including Koreans [42][43][44][45], Chinese [46][47][48], Mexicans [49], Brazilians [50,51], Italians [52], and most strikingly, it was even identified in Greek young (18-20 years) obese men and women [53]. Other studies have linked OSO with various other ill consequences, including cancer and kidney disease; see review [22].…”
Section: Osteosarcopenic Adiposity (Osa) As a Model For Studying And mentioning
confidence: 99%
See 1 more Smart Citation
“…As defined recently by Kelly et al [31], fat mass and fat mass index are included to measure obesity, while waist circumference (WC), visceral fat, visceral/subcutaneous fat ratio, intramuscular adipose tissue by BIA and the android to gynoid fat ratio are used to determine the extent of abdominal/visceral fat. In addition, BIA cutoffs were included as it has been previously used to identify osteosarcopenic obesity, a variant phenotype of obesity, mainly observed in older adults [32].…”
Section: Peri-muscular Fat: a New Entity?mentioning
confidence: 99%
“…Although the preference is to use DXA, BIA and, whenever possible, computed tomography for magnetic resonance imaging to measure ectopic fat mass and to identify osteosarcopenic obesity, a recent systematic review has suggested that the proxy measures of ectopic fat can be easily used in the field or the clinical settings [31]. Finally, the authors have utilized broadly established cutoffs or those of European origin; however, I further encourage adjustments to the criteria for various ethnic groups.…”
Section: Peri-muscular Fat: a New Entity?mentioning
confidence: 99%